Linear Oscillation of the Inter-Connected Satellites Under the Influence of Magnetic Force Oblateness of the Earth and the Shadow of the Earth Due to Solar Radiation Pressure About the Position of Equilibrium for Small Eccentricity Near the Main Resonance - Jha, Nabonarayan; Jha, Jay Narayan (Cognition, 2021)
This paper is devoted to study the non-linear oscillation along the stable position of equilibrium where the system oscillates about the position of equilibrium like a dumb-bell satellite with constant amplitude and phase varying with true anomaly. B.K.M. method has been exploited to get the general solution valid at and near the main resonance n = 1.